2017
DOI: 10.1039/c7cp02303k
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the solubility of graphene oxide in water and alcohols

Abstract: aOne of the main advantages of graphene oxide (GO) over its non-oxidized counterpart is its ability to form stable solutions in water and some organic solvents. At the same time, the nature of GO solutions is not completely understood; the existing data are scarce and controversial. Here, we demonstrate that the solubility of GO, and the stability of the as-formed solutions depend not just on the solute and solvent cohesion parameters, as commonly believed, but mostly on the chemical interactions at the GO/sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 34 publications
3
85
0
Order By: Relevance
“…This fuels non‐fading interest in developing and study of new media for an efficient dispersion of GO, its thermal and chemical reduction to graphene, producing novel functionalized materials. Unfortunately, fundamental investigations of the GO behavior in organic media are limited to a few fundamental papers . A rapid progress in the study of these systems is complicated by a number of factors, including, among others, extremely poor solubility of GO in most of non‐aqueous solvents ,.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This fuels non‐fading interest in developing and study of new media for an efficient dispersion of GO, its thermal and chemical reduction to graphene, producing novel functionalized materials. Unfortunately, fundamental investigations of the GO behavior in organic media are limited to a few fundamental papers . A rapid progress in the study of these systems is complicated by a number of factors, including, among others, extremely poor solubility of GO in most of non‐aqueous solvents ,.…”
Section: Figurementioning
confidence: 99%
“…Unfortunately, fundamental investigations of the GO behavior in organic media are limited to a few fundamental papers. [3][4][5] A rapid progress in the study of these systems is complicated by a number of factors, including, among others, extremely poor solubility of GO in most of non-aqueous solvents. [4,6] In this regard, mixed solvents and in particular organic/water mixtures serve as promising media for dispersing GO and for its modification by means of chemical and physicochemical stresses.…”
mentioning
confidence: 99%
“…Apart from graphene, GO also provide an excellent base for some exciting applications in the field of gas/bio sensing [36,37] and water desalination [38]. The outstanding properties of GO like, dispersibility in water and other solvents [39], large scale fabrication possibility [40], large surface area [41,42] and availability of different functional groups on surface [43] has attracted the interest of research groups. It has been reported that GO surface consists of single sheet with different types of hydrophilic functional groups attached (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) calculations reveal the potential use of metal-free graphene to stabilize ground state molecules through non-covalent π-π interactions 26 . However, pure graphene does not dissolve in organic or inorganic solvents 27 . Thus, researchers have functionalized the graphene surface with epoxy, hydroxyl, or carboxyl groups to obtain readily soluble graphene oxide (GO) 27,28 .…”
mentioning
confidence: 99%